Виявлення причин трудомісткості супроводу корпоративних інформаційних систем - Mozhenkova, Elena V.; Paramonov, Anton I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
The structure of corporate computer networks and the classification of problems by its levels were considered. The main group of elements (application software, system services, and data banks), the corporate information system, is selected as the object of this research. The maintenance stage of corporate information systems is highlighted in the context of labor costs at this stage of the life cycle. For clarity, the process of maintenance is represented by a closed iteration system, where the duration and list of tasks depend on the problem type. In accordance with ISO 14764-2003, the three-level classification is proposed for the types of problems and activities in the maintenance stage of the corporate information system. The statistical analysis was performed of the time costs of maintenance using the proposed classification in the context of tasks and types of errors. Based on the results of the analysis, the main reasons for the complexity of the maintenance of corporate information systems were identified. These reasons determined the main direction of further research - processing of data banks in real time mode for localization of the client’s business process. This will reduce the time and financial costs of maintenance.